The desferrithiocin (DFT) class of iron chelators: Potential as antineoplastic agents - Kicic, Anthony; Chua, A.C.G.; Baker, E. (OXFORD UNIV PRESS, 2001)
Iron (Fe) is essential for the proliferation of cancer cells. A subgroup of the orthosubstituted phenolate class of Fe chelators, desferrithiocin [2-(3′-hydroxypyrid-2′-yl)-4-methyl- Δ2-thiazoline-4(S)-carboxylic acid; DFT] and its analogues, have potential application in short-term chemotherapy for cancer by Fe deprivation. Their effects on cell proliferation, cell cycle progression, Fe uptake and toxicity were therefore examined in adult and fetal rat and human hepatocellular carcinoma (HCC) cell lines, as well as in normal cells. DFT was more active than desferrioxamine, in clinical trials as an antineoplastic agent, consistently inhibiting cell proliferation in all cell lines (IC50 = 40 μM). 2-(2′-hydroxyphenyl-2′-yl)- Δ2-thiazoline-4(S)-carboxylic acid was the most active analogue (IC50 = 55-90 μM). Inhibition was affected by chelator concentration and ability to prevent Fe uptake. The fetal-cell-derived HCC was more susceptible than adult HCC. Structure-activity studies revealed that thiazol methyl deletion greatly diminished antiproliferative activity of the chelators but stereochemical orientation of COOH around C4 had no effect. Removal of the N from the pyridine ring restored antiproliferative activity. Chelators inhibited DNA synthesis in the S phase. The chelators at their IC50 concentration had little or no effect on Fe uptake in normal cells. This apparent selectivity of these chelators for cancer cells, coupled with their high activity, suggests that further investigation is warranted.